AUDIT ANALYSIS AND STUDY OF CONTROLS ON THE BASIS OF THE INTERNATIONAL STANDARD OF ISO 50001 (Academia Science Repository, 2023)
In this article, on the basis of the International ISO 50001 standard, the resources for improving audit efficiency and the creation of necessary conditions for the acceleration of the country's economy, the way of energy-saving development, and one of the implementation methods, the importance of control in the performance of the tasks defined in the "Energy Strategy of Uzbekistan" researched.